Differential Expression of Preoperative Cholestatic Biochemical Profiles, Inflammatory Factors, and Electrolytes: Risk Stratification Based on Complicated GS: Preoperative Biochemical Profiles in Complicated GS - Ge, Xuecui; Zhang, Tingting; Zhang, Changzhou; Liu, Dalu; Zhang, Chun (Journal of Medical Biochemistry, 2026)
Background: Gallstones (GS) are a highly prevalent digestive disorder worldwide and can readily progress to complicated GS. Most previous studies on GS have focused on isolated indicators, while the interplay among multisystem biochemical markers has received far less attention. This gap makes it difficult to fully explain how the disease evolves. The present study was designed to systematically compare preoperative multidimensional biochemical indices between patients with simple GS and those with complicated GS, and to provide laboratory evidence for clarifying the mechanisms underlying disease progression.Methods: A total of 107 patients with GS confirmed by imaging between January 2024 and December 2025 were included, including 49 patients in the simple GS group and 58 in the complicated GS group. The test panel covered five modules: the core cholestatic biochemical profile (10 items), bile duct–specific injury and metabolic regulatory markers (GST-α, C4, and FGF19), inflammation- and tissue remodeling–related markers (10 items), electrolyte and acid-base homeostasis indices (10 items), and 15 bile acid subspecies.Results: The core cholestatic indices were significantly elevated in the complicated group, with TBIL and GGT increasing by 1.87-fold and 4.82-fold, respectively (both P